Attitude Toward Poverty Among Academicians, Social Care Institution Workers And General Population In Kuala-Lumpur, Malaysia - Yasmin Othman Mydin; Fernando Juarez; Dzulkhairi Mohd Rani; Naziha Suliman Abdel Ati; Nazefah Abdul Hamid; Nuruliza Roslan (Atlantis Press, 2024)
Non-Indexed Publication